1973
DOI: 10.1351/pac197333020179
|View full text |Cite
|
Sign up to set email alerts
|

The photoreduction of aromatic systems

Abstract: The irradiation of several aromatic systems (carbocyclic and heterocyclic) in the presence of aliphatic tertiary amines or sodium borohydride leads to the production of dihydro-derivatives. Three different mechanisms for photoreduction have been identified through the use of deuterated species. A system of nomenclature is proposed for categorizing various organic reduction mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 33 publications
(4 reference statements)
1
29
1
Order By: Relevance
“…16 except that the nucleophile is now cyanide ion, formed as a consequence of the photosubstitution reaction. Finally, it is noteworthy that while considerable amounts of 9-cyanophenanthrene (28) and 9-cyano-9,lO-dihydrophenanthrene (29) were isolated from the phenanthrene-photosensitized reactions in acetonitrile solution, no trace of 9-methoxyphenanthrene or the 9-methoxydihydro derivative could be detected in the ~ ~ present system. Apparently the radical cation of phenanthrene (11) is not as susceptible to nucleophilic attack by methanol as by cyanide.…”
Section: Irradiation In Acetonitrile-methanolmentioning
confidence: 77%
“…16 except that the nucleophile is now cyanide ion, formed as a consequence of the photosubstitution reaction. Finally, it is noteworthy that while considerable amounts of 9-cyanophenanthrene (28) and 9-cyano-9,lO-dihydrophenanthrene (29) were isolated from the phenanthrene-photosensitized reactions in acetonitrile solution, no trace of 9-methoxyphenanthrene or the 9-methoxydihydro derivative could be detected in the ~ ~ present system. Apparently the radical cation of phenanthrene (11) is not as susceptible to nucleophilic attack by methanol as by cyanide.…”
Section: Irradiation In Acetonitrile-methanolmentioning
confidence: 77%
“…cules and aliphatic amines the reaction involves electron The half-life of azadirachtin was¯48 min, yielding an transfer [188]. isomerised (Z)-2-methylbut-2-enoate product.…”
Section: Photodegradation Of Napropamide H(rs)-nn-diethyl-2-(1-mentioning
confidence: 99%
“…generated by PET processes from amineϪarene pairs, are known to undergo H ϩ transfer from the α-CϪH bond to the geminate ion radical within the solvent cage, resulting in an amineϪarene adduct through coupling of the resultant radical species. [12] However, we [13] as well as others [14] have reported that PET reactions between a tert-amine and certain potent electron acceptors in polar solvents lead to a sequential two-electron oxidation [electron-proton-electron (E-P-E) sequence] of the amine, leading to iminium cation intermediates. Based on these premises, we have developed a photosystem utilizing 1,4-dicyanonaphthalene (DCN) as a light-harvesting electron-acceptor and methyl viologen dication (MV ϩϩ ) as an electron-transfer mediator, as shown in Figure 1, for the in situ generation of iminium cation intermediates from tert-amines for synthetic purposes.…”
Section: Introductionmentioning
confidence: 94%
“…Nucleophilic alkylation of 3 and 4, using Grignard reagents and allyltrimethylsilane/TiCl4, provides 12a؊d & 15 and 17a؊ c & 21, respectively, in a highly stereoselective manner. Hydrolysis of the resultant amides (12,15,17, and 21) provides α-amino acid derivatives (14) and α-hydroxy acids, respectively, in optically active form, along with the recovered (S)-prolinol chiral auxiliary in its recyclable form. generated by PET processes from amineϪarene pairs, are known to undergo H ϩ transfer from the α-CϪH bond to the geminate ion radical within the solvent cage, resulting in an amineϪarene adduct through coupling of the resultant radical species.…”
Section: Introductionmentioning
confidence: 99%